2000
DOI: 10.1021/bi001141g
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Hexammine Inhibition of the Hammerhead Ribozyme

Abstract: The effects of Co(NH(3))(6)(3+) on the hammerhead ribozyme are analyzed using several techniques, including activity measurements, electron paramagnetic resonance (EPR), and circular dichroism (CD) spectroscopies and thermal denaturation studies. Co(NH(3))(6)(3+) efficiently displaces Mn(2+) bound to the ribozyme with an apparent dissociation constant of K(d app) = 22 +/- 4.2 microM in 500 microM Mn(2+) (0.1 M NaCl). Displacement of Mn(2+) coincides with Co(NH(3))(6)(3+) inhibition of hammerhead activity in 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The slope of the Hill plot was À1.44 AE 0.30. Given that a hexaamminecobalt(III) cation is able to substitute one-to-one for a structurally isomorphous Mg 2 + or Mn 2 + ion, [24] this inhibition slope is consistent with both mono-and dicoordinated manganese ion complexes being catalytically active. The reverse titration was also carried out, in which in the presence of a fixed hexaamminecobalt concentration of 0.5 mM k obs values were measured with progressive titrations of manganese (data not shown).…”
Section: Competition With Hexaamminecobalt Cationsmentioning
confidence: 68%
See 1 more Smart Citation
“…The slope of the Hill plot was À1.44 AE 0.30. Given that a hexaamminecobalt(III) cation is able to substitute one-to-one for a structurally isomorphous Mg 2 + or Mn 2 + ion, [24] this inhibition slope is consistent with both mono-and dicoordinated manganese ion complexes being catalytically active. The reverse titration was also carried out, in which in the presence of a fixed hexaamminecobalt concentration of 0.5 mM k obs values were measured with progressive titrations of manganese (data not shown).…”
Section: Competition With Hexaamminecobalt Cationsmentioning
confidence: 68%
“…[24] Since the hexaamminecobalt(III) cation is substitution-inert with respect to its ammonia ligands (and given that the metalbound ammonia ligands are incapable of the acid-base chemistry characteristic of metal-bound water or hydroxide ligands), competition experiments involving titration with hexaamminecobalt(III) salts into reaction solutions containing a fixed Mg 2 + (or Mn 2 + ) concentration (and vice versa) are able to reveal the catalytic necessity-or not-of Mg 2 + or Mn 2 + . Our competition experiments, carried out on the manganese-utilizing DNAzyme, revealed that the hexaamminecobalt-(III) cation inhibited the RNA cleavage reaction.…”
Section: Competition With Hexaamminecobalt Cationsmentioning
confidence: 99%
“…3A) are significantly lower than those seen in Mg 2+ or other divalent ions at >90% or in sodium or spermidine at 70%-80% ( Fig. 2B ions, with accompanying structural changes, has also been observed in a minimal hammerhead ribozyme (Horton and DeRose 2000).…”
Section: +mentioning
confidence: 73%
“…In the Neurospora crassa VS ribozyme, it enhances activity in the presence of Mg 2+ but cannot support catalysis as the sole metal ion (Maguire and Collins 2001). In the HDV ribozyme (Nakano et al 2000) and in a minimal hammerhead ribozyme (Horton and DeRose 2000), CoHex inhibits activity in the presence of other divalent ions, suggesting a competition for binding. Previous studies with minimal hammerhead ribozymes showed very slow cleavage activity (z0.0071 min…”
Section: Introductionmentioning
confidence: 99%
“…29 These effects have been seen in many ribozyme systems and have been attributed to the excess metal ions causing distortions of ribozyme structure. 41 Monovalent metal ions have also been discussed in the context of ribozyme catalysis. 42 The selection of ATRib (E18) without offering the same catalytic effect.…”
Section: Inhibition By Metal Ionsmentioning
confidence: 99%